2020
DOI: 10.1044/2020_ajslp-19-00156
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Input and Child Language Comprehension During Book Reading in Children With Down Syndrome

Abstract: Purpose Communication interactions between parents and children during shared book reading impact a child's development of both language and literacy skills. This study examined maternal language input and child expressive communication during a shared book reading activity in children with Down syndrome (DS) and children with typical development (TD). Additionally, children's receptive language was examined to understand the relationship between maternal language input and child receptive language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
7
10
0
Order By: Relevance
“…Previous findings show that in order for shared book reading to support growth in child language, it is not sufficient to merely read the text of the book (Landry et al., 2012). Rather, parents need to make reading engaging by ‘scaffolding the language of the book for optimal engagement and reciprocal communication’ (Barton‐Hulsey et al., 2020 p. 1476). For typically developing children who are verbal, there are a number of established techniques that have been reported to achieve this, such as those outlined in the process of dialogic reading (e.g., using questions to encourage the child to talk about the pictures, providing informative feedback using expansions and corrective modelling [Mol et al., 2008]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous findings show that in order for shared book reading to support growth in child language, it is not sufficient to merely read the text of the book (Landry et al., 2012). Rather, parents need to make reading engaging by ‘scaffolding the language of the book for optimal engagement and reciprocal communication’ (Barton‐Hulsey et al., 2020 p. 1476). For typically developing children who are verbal, there are a number of established techniques that have been reported to achieve this, such as those outlined in the process of dialogic reading (e.g., using questions to encourage the child to talk about the pictures, providing informative feedback using expansions and corrective modelling [Mol et al., 2008]).…”
Section: Discussionmentioning
confidence: 99%
“…Parents report a lack of motivation and attention during shared book reading and highlight these factors as significant barriers when reading with their child with Down syndrome (Lusby & Heinz, 2020). This passivity can result in parents taking on a more directive role and is corroborated by findings that compared to mothers of typically developing children, mothers of children with Down syndrome use more utterances and ask more questions to try and engage their child in greater communication (Barton‐Husley et al., 2020).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…With parents as partners, rich home literacy environments can be used to support the development of phonological awareness, vocabulary, syntax, and print conventions in young children with DS. 45 For example, Barton-Hulsey et al 46 reported that mothers of children with DS (22-63 months) provided the same amount of vocabulary input as mothers of children with typical development during shared book reading, used more words for descriptive purposes, and simplified their syntax to meet their child's developmental needs. Similarly, in a 6-week shared book reading intervention, Van Bysterveldt et al 47 taught parents of 4-year-old children with DS to provide explicit instruction in letter knowledge, letter-sound knowledge, and initial phoneme identification (e.g., /s/ is the first sound in "spot").…”
Section: Support For Prereadingmentioning
confidence: 99%